Analysis of salient-pole synchronous generators operating in single-phase condition - Spagnolo, C.; Nuzzo, Stefano; Serra, G.; Gerada, C.; Galea, Michael (2017)
The power generation industry has recently started to invest interest and focus on the single-phase operation of traditional three-phase, wound-field, synchronous generators. This is partially due to a combination of customer requirements and the need to understand the extent of flexibility in their current products. This paper deals with an in-detail analysis of a salient-pole, wound-field, three-phase synchronous generator operating in single-phase condition, at unity power factor. The particular 400kVA alternator is first analysed via the classical analytical equations and the results compared with finite-element and available experimental measurements for validation purposes. The tools developed in this stage are then used to analyse the generator under study when it operates in single-phase condition with different values of load. In this work, it can be observed how single-phase operation of synchronous generators can result in an increase of the power-per-phase performance and that, with the appropriate winding configuration, the machine can be used in single-phase operation with a reduced loading.